2012
DOI: 10.1523/jneurosci.6036-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Taste Preference and Acceptability: Quality versus Hedonics

Abstract: Several methods exist for reliably determining the motivational valence of a taste stimulus in animals, but few to determine its perceptual quality independent of its apparent affective properties. Individual differences in taste preference and acceptability could result from variance in the perceptual qualities of the stimulus leading to different hedonic evaluations. Alternatively, taste perception might be identical across subjects whereas processing of the sensory signals in reward circuits could differ. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…1). This confirms previous reports that SA detect a concentration-dependent aversive taste quality in sucralose [12, 19, 20]. Our current study further revealed that SA switched from drinking sucralose to drinking water approximately 60% of the time at concentrations of sucralose that they avoid (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…1). This confirms previous reports that SA detect a concentration-dependent aversive taste quality in sucralose [12, 19, 20]. Our current study further revealed that SA switched from drinking sucralose to drinking water approximately 60% of the time at concentrations of sucralose that they avoid (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These data provide clear evidence that SA detect a bitter-like taste quality in normally avoided sucralose concentrations. SP also licked more to sucralose than SA in a briefaccess paradigm at these same concentrations [19]. Taken together, these findings confirm that differences in sensory (taste-guided) processing are sufficient to explain the differential acceptance of sucralose in SP and SA.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations